APLIKASI PERHITUNGAN HARTA WARISAN BERDASARKAN HUKUM ISLAM - Rahmadanilah Rahmadanilah; Yulianto T Polly; Adriana Fanggidae (J-ICON : Jurnal Komputer dan Informatika, 2016)
Heritage is something that is inherited, such as property, reputation, etcetera. In the daily lives, legacy issues often trigger conflicts and raises a family relationship. The main cause is human greed, and beyond this the lack of knowledge of the relevant parties regarding the calculation of inheritance law. Many Muslims do not know the law and how the calculation is based on the Islamic law of inheritance. To overcome these problems then built an application to assist in the calculation of the legacy based on Islamic Law following that Islamic Law rules. This application produces the percentage and nomina which received by each heirs.